Whole‐exome sequencing diagnosis of two autosomal recessive disorders in one family. (7th March 2015) - Takeichi, T.; Nanda, A.; Aristodemou, S.; McMillan, J.R.; Lee, J.; Akiyama, M.; Al‐Ajmi, H.; Simpson, M.A.; McGrath, J.A.
Summary Autosomal recessive congenital ichthyosis (ARCI) is a genetically heterogeneous disorder for which subtyping through molecular analysis can help determine the eventual phenotype and prognosis. We used whole‐exome sequencing to identify a new homozygous splice‐site mutation in ST14 (IVS5+1G>A), encoding matriptase, in a 4‐year‐old girl with ARCI from a consanguineous Kuwaiti family. Clinically, she also had hypotrichosis, which supported a diagnosis of ARCI type 11. Only four previous examples of pathogenic mutations in ST14 have been reported, and our findings expand the genotype–phenotype correlation for this subtype of ARCI. Our patient was the second child born to these parents; the first (deceased) and third children had congenital brain and eye abnormalities, of uncertain aetiology and with no precise diagnosis. Further analysis of our patient's exome dataset revealed heterozygosity for a splice‐site mutation in POMT1 (IVS4+1G>T), encoding the protein O‐mannosyltransferase, a gene implicated in Walker–Warburg syndrome. DNA sequencing in the third child showed homozygosity for this mutation in POMT1. The first‐cousin parents were both heterozygous for the splice‐site mutations in ST14 and POMT1. In this family, whole‐exome sequencing provided accurate subtyping of a form of ARCI in one child and provide an explanation for an undiagnosed developmental disorder in two other children, findings that improve the prospects for diagnostic accuracy and genetic counselling, and demonstrate the impact of next‐generation sequencing technologies on clinical genetics.